Pendidikan Akhlak Melalui Dakwah bil Uswah di Pondok Pesantren - Yakin, Aenul; Nur, Tajuddin (Dakwah, 2022)
Abstract Moral education in Islam is education that recognizes that good preaching is needed in human life and must be taught by Islamic boarding schools. By instilling good morals so that you can become an example if you graduate. At this time, the most important thing is to set an example in preaching, or it can be said to be Da’wah Bil Uswah. This article will discuss Da'wah Bil Uswah, and this type of research is qualitative research. The subjects of this study were caregivers, ustadz, and students of Pondok Pesantren At-Taubah Karawang. The place of research was conducted at Pondok Pesantren At-Taubah Karawang. The data collection method uses observation, interview, and documentation techniques. Furthermore, the data is presented in an appropriate form to read and understand. Then the data is analyzed, and conclusions are drawn. The results of this study state that 1) The implementation of the concept of Imam Al Ghazali's Moral education is categorized as having a good implementation, indicated by the contribution of caregivers and ustadz making the schedule for the Koran and scientific contributions; 2) Efforts made by caregivers and ustadz in implementing the concept of moral education through Dakwah bil Uswah at Pondok Pesantren At-Taubah Karawang, namely: a) Providing guidance; b) Giving Tausiyah; c) Providing exemplary; d) Applying habituation; 3) Supporting factors in implementing the concept of moral education at Pondok Pesantren At-Taubah Karawang, namely: a) Cooperation between caregivers and ustadz; b) Parental Support; c) Facilities. 4) The inhibiting factors in implementing the concept of moral education at Pondok Pesantren At-Taubah Karawang are a) Worldly nature; b) Limited Facilities and Infrastructure. Keywords; Concept of Moral Education, Pupils, Boarding Schools, Dakwah bil Uswah